2001
DOI: 10.1128/jb.183.18.5395-5401.2001
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Overproduction AffectsPseudomonas aeruginosaBiofilm Structure and Function

Abstract: During the course of chronic cystic fibrosis (CF) infections, Pseudomonas aeruginosa undergoes a conversion to a mucoid phenotype, which is characterized by overproduction of the exopolysaccharide alginate. Chronic P. aeruginosa infections involve surface-attached, highly antibiotic-resistant communities of microorganisms organized in biofilms. Although biofilm formation and the conversion to mucoidy are both important aspects of CF pathogenesis, the relationship between them is at the present unclear. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
520
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 599 publications
(545 citation statements)
references
References 55 publications
(51 reference statements)
20
520
2
3
Order By: Relevance
“…Fourier transform infrared spectroscopy (FTIR) demonstrated that alginate was associated with biofilms of this mucoid strain. Similar results were obtained using a mutant derivative of the nonmucoid strain P. aeruginosa PAO1 engineered to overproduce alginate (25,60). On the other hand, results using wild-type P. aeruginosa PAO1 and PA14 showed that alginate was not associated with biofilms (72) and that a second polysaccharide likely encoded by a separate polysaccharide biosynthetic gene cluster may provide the extracellular matrix material for those cells (18,19,29).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Fourier transform infrared spectroscopy (FTIR) demonstrated that alginate was associated with biofilms of this mucoid strain. Similar results were obtained using a mutant derivative of the nonmucoid strain P. aeruginosa PAO1 engineered to overproduce alginate (25,60). On the other hand, results using wild-type P. aeruginosa PAO1 and PA14 showed that alginate was not associated with biofilms (72) and that a second polysaccharide likely encoded by a separate polysaccharide biosynthetic gene cluster may provide the extracellular matrix material for those cells (18,19,29).…”
supporting
confidence: 69%
“…P. aeruginosa pulmonary infections are considered biofilm-associated diseases, where the bacteria colonize the surface of pulmonary tissue (36), are often encapsulated in extracellular polysaccharide matrix material (25,36,48), secrete quorumsensing signaling compounds (58), and have increased resistance to antibiotics (reviewed in reference 59) and to host defenses (2,30,45). Mutations in the cystic fibrosis transmembrane regulator of CF patients lead to physiological alteration of pulmonary fluid, with the most characteristic manifestation being the increased concentrations of thick pulmonary mucus that includes DNA and actin from lysed neutrophils (38).…”
mentioning
confidence: 99%
“…2B). This corresponds to observations done in surface-attached biofilms, where biofilms formed by mucoid P. aeruginosa have been shown to be more difficult to eradicate than the corresponding wild-type biofilms (18), while the MIC values for planktonic cultures were comparable (10). Deletion of the algD gene in the mucA background resulted in nonmucoid No statistical differences in survival were observed between the two strains upon antimicrobial treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilms of mucoid P. aeruginosa strains are more tolerant to antibiotics than wild-type biofilms (10), and mucoidy has been implicated in increased tolerance to host immune responses (11).…”
mentioning
confidence: 99%
“…Biofilm protects the cell against mercury toxicity Many bacteria are embedded in an extracellular polymeric substance matrix composed of polysaccharides, proteins, and nucleic acids (Flemming and Wingender, 2001). The surfaceattached communities (biofilms) increase resistance to antimicrobial agents compared to the resistance of free-swimming organisms (Hentzer et al, 2001) probably due to decreased metabolic activity within the depths of a biofilm (Spoering and Lewis, 2001) and to binding and sequestration of antimicrobial agents by biofilm components, such as negatively charged phosphate, sulfate, and carboxylic acid groups (Hunt, 1986). As biofilms facilitate sorption of heavy metals, they are capable of removing heavy metal ions from bulk liquid (Liehr et al 1994;Labrenz et al, 2000).…”
Section: The Mercury Uptake Is Ph-dependentmentioning
confidence: 99%